Risk categories and risk management processes in nonprofit organizations - Jarosław Domański (Foundations of Management, 2016)
The article addresses risk management in nonprofit organizations. This topical issue appears not to have been adequately studied by researchers to date. There are several questions the author of this paper attempts to answer: What are the risk categories faced by nonprofit organizations in their daily operations? Do Polish nonprofit organizations take any measures in the area of strategic risk management? A contribution is made to the theory of management of nonprofit organizations by making an overview of existing literature on the subject, identifying a research gap, proposing concepts that attempt to fill the gap, and recommending areas for future study. A comprehensive list of risks faced by nonprofit organizations in their daily operations has been developed and validated for further application. The empirical material comes from a study based on a national random sample of 235 nonprofit organizations.
Keywords: 650; risk management; nonprofit organizations; strategic management; risk management process